Ochratoxicosis in Broiler Chickens: Functional and Histological Changes in Target Organs - Elaroussi, M.A.; Mohamed, F.R.; Elgendy, M.S.; El Barkouky, E.M.; Abdou, A.M.; Hatab, M.H. (International Journal of Poultry Science, 2008)
This experiment was conducted to evaluate the effects of ochratoxin A (OTA) on the function and histology of the liver, kidney and bursa of broiler chickens fed OTA contaminated rations. Two hundred forty one-day-old male Ross broiler chicks were used, they were randomly divided into 3 dietary experimental groups of 80 birds and given rations containing 0 (control), 400 or 800 μg OTA/Kg feed. The chicks were maintained on these treatments through 5 weeks of age with feed and water available for ad libitum intake throughout the experimental duration. Dietary OTA contamination at both levels resulted in significant increase (P < 0.05) in the relative weights of kidney and liver and in serum glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), uric acid and creatinine levels in OTA treated birds as compared to the control. A significant decrease (P < 0.05) was found in bursa of Fabricius weight, serum antibody (Ab) titres against Newcastle disease virus (NDV) and in serum total protein, albumin and globulin of the OTA treated groups as compared to the control. Histological examination revealed marked degenerative changes in the kidney and bursa and mononuclear cell infiltration was recorded in the liver of broilers exposed to OTA contamination. All of the above changes became more evident with the higher OTA level and with prolongation of experimental period. Therefore, these results indicate that exposure to OTA at concentration ≥ 400 ppb could adversely affect kidney, liver and bursa function and histology and thus broiler performance and health.